2019
DOI: 10.1039/c8mt00307f
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the mitochondrion by dinuclear thiolato-bridged arene ruthenium complexes in cancer cells and in the apicomplexan parasite Neospora caninum

Abstract: Dinuclear ruthenium complexes inhibit N. caninum and specifically target the parasite mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 74 publications
(113 reference statements)
3
53
0
Order By: Relevance
“…For instance, endochin-like quinolones affect the ultrastructure of mitochondria-as evidenced by digestive vacuoles containing mitochondrial fragments-but not of other organelles in N. caninum tachyzoites [24]. In addition, organometallic ruthenium complexes were shown to primarily act on mitochondria in Toxoplasma gondii [25], N. caninum [26], and in the extracellular protozoan parasite Trypanosoma brucei [27].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, endochin-like quinolones affect the ultrastructure of mitochondria-as evidenced by digestive vacuoles containing mitochondrial fragments-but not of other organelles in N. caninum tachyzoites [24]. In addition, organometallic ruthenium complexes were shown to primarily act on mitochondria in Toxoplasma gondii [25], N. caninum [26], and in the extracellular protozoan parasite Trypanosoma brucei [27].…”
Section: Discussionmentioning
confidence: 99%
“…Dinuclear tris(thiolato)-bridged arene complexes are typically obtained from the reaction of the precursor [(arene)MCl(µ2-Cl)2M(arene)Cl] M = Fe, Ru, Rh, Os, Ir with thiolate compounds and represent an interesting class of organometallic compounds. Iron complexes serve as carbon-halogen bond activation reagents, and carbon-halogen bond-cleavage agents, [1][2][3][4] while osmium 5 , iridium, rhodium [6][7][8][9][10][11][12] and especially ruthenium complexes 13,14,[23][24][25][15][16][17][18][19][20][21][22] have in vitro antiproliferative activity against cancer cell lines and several protozoan parasites. Tris(thiolato)-bridged dimolybdenum complexes are also readily available but are synthesised using other strategies such as the direct oxidation of low-valence carbonyl precursors or reductive process from higher-valence derivatives, [26][27][28] which will not be discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…44,46 Dinuclear thiolatobridged arene ruthenium complexes are also promising as antiprotozoal agents, with IC50 values of up to 1.2 nM against T. gondii, N. Caninum and T. Brucei and IC50 values against human foreskin fibroblasts > 800 µM, leading to selectivity indexes > 20'000. 16,17,47 The current synthesis route for obtaining dinuclear cationic trithiolato bridged arene ruthenium complexes of the general formula [(η 6 -p-MeC6H4Pr i )2Ru2(µ2-S-R)3] + with good yields dates back to the early 2000s and involves the reaction of the dimer [(η 6 -p-MeC6H4Pr i )Ru(µ2-Cl)Cl]2 with an excess of the corresponding thiol (see Scheme 1) usually in refluxing ethanol (EtOH). 37 For thiophenolato complexes, depending on the thiophenol used, it is possible to adjust the conditions to direct the synthesis exclusively to the cationic trithiophenolato complex [(η 6 -p-MeC6H4Pr i )2Ru2(µ2-SC6H4-R)3] + , 15 the neutral dithiophenolato complex [(η 6 -p-MeC6H4Pr i )2Ru2(µ2-SC6H4-R)2Cl2], 48 or even the neutral monothiophenolato complex [(η 6 p-MeC6H4Pr i )2Ru2Cl2(µ-Cl)(µ2-SC6H4-R)].…”
Section: Introductionmentioning
confidence: 99%
“…Though it was found that DiRu-1 has the ability to catalyze glutathione (GSH) oxidation, this mechanism can only explain its cytotoxicity to a certain extent. Recently, it was found that, when using inductively coupled plasma mass spectrometry (ICP-MS), 97% of the ruthenium is localized in the mitochondria of treated A2780 cells [9,10,11].…”
Section: Introductionmentioning
confidence: 99%